THE ROLE OF ORDER MANAGEMENT SYSTEM IN SUPPORTING DIGITAL TRADE FACILITATION AND GLOBAL MARKETING STRATEGY (CASE STUDY OF PT KOMATSU UNDERCARRIAGE INDONESIA) - Safitri, Nisak Erik; Dewi, Liliana; Christian, Timotius Febry (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
The Study examines the role of integration of an Order Management System (OMS) in supporting digital trade facilitation and strengthening global marketing strategy at PT Komatsu Undercarriage Indonesia in collaboration with Komatsu Australia. Before OMS implementation, order handling relied on manual processes in which purchase orders were sent via email or PDF and re-entered into internal systems, resulting in fragmented orders across multiple Australian destinations, requiring cross-country clarifications of up to two to three days, resulting in increased risks of errors and administrative delays. The research employed a qualitative descriptive case study approach, collecting primary data through semi-structured interviews, direct observation, and documentation review. Data were analyzed using NVivo to support systematic coding theme development and pattern visualization. The findings indicate that OMS acts as a key enabler of upstream digital trade facilitation by standardizing order formats, improving data accuracy, reducing duplication or missing orders, and enhancing near real-time visibility and coordination between KUI and Komatsu Australia. Furthermore, OMS provides an integrated single source of truth for demand and marketing strategy. The study concludes that OMS integration improves cross-border information flow and operational reliability, although organizational readiness and data governance remain critical to maximizing long-term strategic benefits.